Penapisan Tiga Puluh Tujuh Genotipe Tomat dan Seleksi Primer RAPD untuk Toleransi terhadap Layu Bakteri (Ralstonia solanacearum) - Adeputri, Eriana; Rustikawati, Rustikawati; Herison, Catur (Akta Agrosia, 2016)
Bacterial wilt (Ralstonia solanacearum) is the most important tomato diseases which can reduce tomato yield up to 100%. One most prospective control measure is the development of high yielding varieties tolerance to bacterial wilt. Donor parent carrying bacterial wilt controlling gene(s) is required to develop such varieties. The objectives of this study were to screen thirty-seven tomato genotypes for tolerance to R. solanacearum and to obtain RAPD markers of resistance to bacterial wilt. The experiment was arranged without the experimental design. Each tomato genotypes consisting of 5 control uninoculated plants and 10 plants were inoculated with R. solanacearum with a concentration of 106 cfu / ml inoculum of 10 mL per plant. Scoring was done on the severity of disease symptom; and the plants were grouped according to scoring class. Molecular analysis was done by using Bulk Segregant Analysis (BSA). The results showed there were six genotypes considerd very tolerant i.e. genotype Pearl, Opal, Cung, Syu and Kudamati I; tolerant genotypes consisting of five genotypes; medium tolerant groups consisting of eight genotypes; medium sensitives groups consisting of 14 genotypes; and sensitive class consisting of four genotypes, namely Aceh Local Tomatoes I, Tanah Datar Local Tomato, Tomato Meranti I and Tomato Meranti II. Of the 20 primers used only 8 primers showed visible DNA bands, they were E1, E7, E10, H2, H5, H13, H16 and H19. However there no polymorphics bands observed for bacterial wilt tolerance.